The influence of radio frequency‐based toothbrush on the accumulation of calculus and periodontal health: A randomized double‐blind controlled prospective study - Juan Khoury; Hadar Z. Giladi; Ofir Ginesin; Eran Gabay; Yaniv Mayer (Wiley, 2023)
Abstract Objectives The use of a toothbrush with radio frequency (RF) has shown to be of benefit regarding the reduction of plaque, calculus, and dental staining and improving teeth shade compared to conventional powered and manual toothbrushes. Aim: To evaluate the efficacy of the RF toothbrush in the reduction of calculus accumulation and its effect on periodontal parameters as well as subject satisfaction as compared to an identical sham‐tooth brush. Materials and Methods Patients who are under a strict maintenance program were included. Patients were allocated to test (RF toothbrush) or control (sham) randomly and were examined at baseline, one and three months. Clinical photos were taken and a consequential calculus assessment via ImageJ software. Clinical assessment included the following: plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD), and recession (REC). Patient satisfaction was assessed via a questionnaire. Results Fifty‐eight patients (29 control, 29 test) were included. At baseline mean PPD, BOP, PI, REC, and calculus accumulation were similar between the groups. Mean buccal calculus was lower in the test group at one month 4.0% versus 6.7%, p < .05. Calculus accumulation within the groups was lower in the test group at 1 and 3 months when compared to baseline at the buccal aspect (2.8% vs. 8.9%, p < .05% and 3.8% vs. 8.9%, p < .05) and lingual aspect (6.7% vs. 16.5%, p < .05% and 8.9% vs. 16.5%, p < .05). No statistically significant results were found regarding periodontal parameters PPD, BOP, PI, and REC. No difference was found between groups regarding patient satisfaction. Conclusion RF seems to have an additive effect on preventing calculus accumulation on the buccal aspect of anterior mandibular teeth at 1 month. Nevertheless, at 3 months, no difference between the toothbrushes is seen regarding calculus formation and maintaining periodontal health (ClinicalTrials.gov, Identifier NCT04640857).